The Philosophy Meaning of the Lebaran Ketupat Tradition in Javanese Society - Vinata, Dinda; Dora, Nuriza (Journal of Social Work and Science Education, 2025)
This research aims to reveal the philosophical meanings contained in the Ketupat Eid tradition among the Javanese community in Dolok Malela Village. Ketupat Eid is a tradition held after the Idul Fitri celebration as a form of gratitude for successfully observing the fasting during the month of Ramadan. In this study, a qualitative approach using case study methods was employed to explore the cultural, religious, and social values behind the implementation of this tradition. The findings indicate that the Ketupat Eid tradition has deep symbolic meanings. Ketupat, as a symbol of the success in performing the fast, represents purity, peace, and togetherness. Furthermore, the process of making and presenting ketupat during this celebration embodies a philosophy about the relationship between humans and God, among fellow humans, and with nature. The people of Dolok Malela Village interpret this tradition as a means to strengthen the ties of friendship, build social solidarity, and revive the values of mutual cooperation in daily life. Ketupat Lebaran also functions as an effort to preserve the culture and identity of the Javanese community in the village. This tradition not only has a religious dimension but also contains social meanings that teach the importance of togetherness, tolerance, and care for one another. This research concludes that the Ketupat Lebaran tradition in Dolok Malela Village plays an important role in strengthening the social and cultural structure of the community while also teaching life values that are relevant to the challenges of the times.